Hybrid electronic record: An error reduction strategy for diverse medical prescription formats - Carl-Heinz Kruse; Michelle T.D. Smith; Damian L. Clarke (South African Family Practice)
Background: This project is part of a broader effort to develop a new electronic registry for ophthalmology in the KwaZulu-Natal (KZN) province in South Africa. The registry should include a clinical decision support system that reduces the potential for human error and should be applicable for our diversity of hospitals, whether electronic health record (EHR) or paper-based.